FAKTOR RESIKO PENYAKIT DEMAM BERDARAH DENGUE (DBD) DI WILAYAH KERJA PUSKESMAS BANTUL I KABUPATEN BANTUL PROVINSI YOGYAKARTA TAHUN 2017 - Ervin Nur Wahyuliati; Yulian Endarto (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
Background :.There were 115 dangue fever cases at Public Health Center Bantul 1 in 2016. However in its development had a significant increase from the previous year in 2015 there were 9 cases Dengue Fever in PalbapangVillage and Trirenggo Village there were no reports of Dengue Fever Cases. Whereas for disease reporting was still manual. It meant that all of the cases were only recorded in Mocrosot Excel tables and did not used mapping system with GIS that can make it easier to analyze exiting information. Objective: The aim of this research is to describe risk factor of dengue fever spatially in helth center work area Bantul 1, in order to make it easier in decide on intervention given has and as needed. Methods: The type of research used in this study in quantitative descriptive with cross sectional research design. Spatial analysis using ArcView software. The research sampel was 55. Data were analyzed by using Chi Square test. Result : Rich factor mapping which was devided into 10 spatial analysis of risk factors or dengue fever and 1 map buffer of mosquito fly distance 200 meter showed that clustering patterns. Bivariate analysis showed that there was a correlation between environmental factors and behavioral factors with the incidence of dengue fever in the Health Center in work area of Bantul 1                        Conclusion: There was correlation between environmental factors and behavioral factors with the incidence of dengue fever in the Health Center work area of Bantul 1. Keywords: Dengue Fever, GIS (Geographic Information System)